An object is said to be moving with a uniform acceleration if its velocity changes by equal amounts in equal intervals of time.
Formulae for uniformly accelerated motion along a straight line
Consider an object, moving with a uniform acceleration ‘a‘ along a straight line OX, with origin at O. Let the object reach at points A and B at instants $ \displaystyle {{t}_{1}}\text{ and }{{t}_{2}}$. Let $ \displaystyle {{x}_{1}}\text{ and }{{x}_{2}}$ be the displacements of the object at time $ \displaystyle {{t}_{1}}\text{ and }{{t}_{2}}$ respectively and $ \displaystyle {{v}_{1}}\text{ and }{{v}_{2}}$ be the velocity of the object at position A and B respectively.
(i) Velocity-time relation
$ \displaystyle \because \text{acceleration }=\dfrac{{\text{change of velocity}}}{{\text{time taken}}}$
$ \displaystyle \begin{array}{l}\therefore a=\dfrac{{{{v}_{2}}-{{v}_{1}}}}{{{{t}_{2}}-{{t}_{1}}}}\text{ }…\text{(1)}\\\Rightarrow {{v}_{2}}-{{v}_{1}}=a\left( {{{t}_{2}}-{{t}_{1}}} \right)\\\Rightarrow {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)\text{ }…\text{(2)}\end{array}$
Let origin of time axis be taken at A and $ \displaystyle u$ be the velocity of the object at A and $ \displaystyle v$ be velocity of the object at B after time t. Then
$ \displaystyle \begin{array}{l}{{v}_{1}}=u;{{t}_{1}}=0;{{v}_{2}}=v\\\text{and }{{t}_{2}}=t\end{array}$
Putting values in (2), we get
$ \displaystyle v=u+at$
The relations (2) and (3) are required velocity-time relations.
(ii) Position-time relation
Let $ \displaystyle {{v}_{{av}}}$ be the average velocity of the object during the motion of the object from A to B,
$ \displaystyle {{v}_{{av}}}=\dfrac{{\text{total displacement}}}{{\text{total time taken}}}=\dfrac{{{{x}_{2}}-{{x}_{1}}}}{{{{t}_{2}}-{{t}_{1}}}}$
$ \displaystyle \begin{array}{l}\text{or }{{x}_{2}}-{{x}_{1}}={{v}_{{av}}}\left( {{{t}_{2}}-{{t}_{1}}} \right)\\\text{But, }{{v}_{{av}}}=\dfrac{{\text{initial velocity + final velocity}}}{2}\\=\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}\end{array}$
$ \displaystyle {\therefore {{x}_{2}}-{{x}_{1}}=\left( {\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)\text{ }…\text{(4)}}$
$ \displaystyle {\text{or }{{x}_{2}}={{x}_{1}}+\left( {\dfrac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)}$
$ \displaystyle {\because {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)}$
$ \displaystyle \begin{array}{l}\therefore {{x}_{2}}={{x}_{1}}+\\\left( {\dfrac{{{{v}_{1}}+\left( {{{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)} \right)}}{2}} \right)\left( {{{t}_{2}}-{{t}_{1}}} \right)\end{array}$
$ \displaystyle \begin{array}{l}\Rightarrow {{x}_{2}}={{x}_{1}}+\\{{v}_{1}}\left( {{{t}_{2}}-{{t}_{1}}} \right)+\frac{1}{2}a{{\left( {{{t}_{2}}-{{t}_{1}}} \right)}^{2}}\ldots \text{(5)}\end{array}$
If $ \displaystyle {{x}_{0}},u$ are the displacement and velocity of the object at $ \displaystyle {{t}_{1}}=0$ and x be the displacement of object at t, then using $ \displaystyle {{t}_{1}}=0,\text{ }{{x}_{1}}={{x}_{0}},\text{ }{{v}_{1}}=u,\text{ }{{t}_{2}}=t\text{ and }{{x}_{2}}=x$ in relation (5), we have
$ \displaystyle \begin{array}{l}x={{x}_{0}}+u\left( {t-0} \right)+\dfrac{1}{2}a{{\left( {t-0} \right)}^{2}}\\\Rightarrow x={{x}_{0}}+ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(6)}\\\Rightarrow x-{{x}_{0}}=ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(7)}\end{array}$
Using, $ \displaystyle x-{{x}_{0}}=S=$ distance travelled in time t, we have
$ \displaystyle S=ut+\dfrac{1}{2}a{{t}^{2}}\text{ }…\text{(8)}$
The relation (5), (6) and (8) are required position-time relations.
Using relation (6), the position-tie graph for positive and negative accelerations are shown in the image below. These graphs have parabolic shapes.
Positive acceleration:
Negative acceleration (Deceleration):
(iii) Position-velocity relation
Since,
$ \displaystyle {{v}_{2}}={{v}_{1}}+a\left( {{{t}_{2}}-{{t}_{1}}} \right)$
we have
$ \displaystyle \left( {{{t}_{2}}-{{t}_{1}}} \right)=\dfrac{{{{v}_{2}}-{{v}_{1}}}}{a}$
Putting this value in equation (4), we get
$ \displaystyle \begin{array}{*{20}{l}} \begin{array}{l}{{x}_{2}}-{{x}_{1}}=\left( {\frac{{{{v}_{1}}+{{v}_{2}}}}{2}} \right)\left( {\frac{{{{v}_{2}}-{{v}_{1}}}}{a}} \right)\\\Rightarrow {{x}_{2}}-{{x}_{1}}=\frac{{v_{2}^{2}-v_{1}^{2}}}{{2a}}\end{array} \\ {\Rightarrow v_{2}^{2}-v_{1}^{2}=2a({{x}_{2}}-{{x}_{1}})\text{ }…\text{(9)}} \end{array}$
If u and v are the velocities of an object at positions $ \displaystyle {{x}_{0}}\text{ and }x$ respectively, then using $ \displaystyle {{v}_{1}}=u$,
$ \displaystyle {{v}_{2}}=v,\text{ }{{x}_{1}}={{x}_{0}}\text{ and }{{x}_{2}}=x$ in (9), we get
$ \displaystyle {{v}^{2}}-{{u}^{2}}=2a\left( {{{x}_{0}}-x} \right)\text{ }…\text{(10)}$
If $ \displaystyle x-{{x}_{0}}=S$, then
$ \displaystyle {{v}^{2}}={{u}^{2}}+2aS\text{ }…\text{(11)}$
The relations (9), (10) and (11) are the required position-velocity relations.